Alterations to the Lung Microbiome in Idiopathic Pulmonary Fibrosis Patients - Tong, Xunliang; Su, Fei; Xu, Xiaomao; Xu, Hongtao; Yang, Ting; Xu, Qixia; Dai, Huaping; Huang, Kewu; Zou, Lihui; Zhang, Wenna; Pei, Surui; Xiao, Fei; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Lung microbiome ecosystem homeostasis in idiopathic pulmonary fibrosis (IPF) remains uncharacterized. The aims of this study were to identify unique microbial signatures of the lung microbiome and analyze microbial gene function in IPF patients. DNA isolated from BALF samples was obtained for high-throughput gene sequencing. Microbial metagenomic data were used for principal component analysis (PCA) and analyzed at different taxonomic levels. Shotgun metagenomic data were annotated using the KEGG database and were analyzed for functional and metabolic pathways. In this study, 17 IPF patients and 38 healthy subjects (smokers and non-smokers) were recruited. For the PCA, the first and the second principal component explained 16.3 and 13.4% of the overall variability, respectively. The β diversity of microbiome was reduced in the IPF group. Signature of IPF's microbes was enriched of Streptococcus, Pseudobutyrivibrio, and Anaerorhabdus. The translocation of lung microbiome was shown that 32.84% of them were from oral. After analysis of gene function, ABC transporter systems, biofilm formation, and two-component regulatory system were enriched in IPF patients' microbiome. Here we shown the microbiology characteristics in IPF patients. The microbiome may participate in altering internal conditions and involving in generating antibiotic resistance in IPF patients.